2016
DOI: 10.1093/jnci/djw028
|View full text |Cite
|
Sign up to set email alerts
|

Targeting a Cancer-Specific Epitope of the Epidermal Growth Factor Receptor in Triple-Negative Breast Cancer

Abstract: Background: Triple-negative breast cancers (TNBCs) are typically more aggressive and result in poorer outcomes than other breast cancers because treatment options are limited due to lack of hormone receptors or amplified human epidermal growth factor receptor 2 (HER2). Many TNBCs overexpress the epidermal growth factor receptor (EGFR) or manifest amplification of the EGFR gene, supporting EGFR as a therapeutic target. While EGFR-directed small molecule inhibitors have shown limited effectiveness in clinical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The addition of everolimus was well tolerated; however, it did not lead to any significant improvement in terms of RR (48% vs. 30% in favor of everolimus) and pathological CR (30% vs. 26% in favor of everolimus) [Gonzalez-Angulo et al, 2011]. Despite triple negative BC is HER2-, everolimus has been examined in a regimen with anti-HER2 agents since EGFR is high-amplified in $50% of triple negative BC tumors [Reis-Filho and Tutt, 2008;Simon et al, 2016], providing a robust rationale for exploration the association between an anti-EGFR and a mTOR inhibitor to determine overlap in the tumors that were refractory to anti-EGFR drugs [Gogineni and DeMichele, 2012;Passiglia et al, 2015]. Though the mTOR inhibitors paradoxically stimulate the AKT pathway [Sun et al, 2005], this activation could probably serve as a mechanism for resistance to mTOR inhibitors [Hahn et al, 2009;Jerusalem et al, 2014].…”
Section: Mtor Inhibitors In Bcmentioning
confidence: 99%
“…The addition of everolimus was well tolerated; however, it did not lead to any significant improvement in terms of RR (48% vs. 30% in favor of everolimus) and pathological CR (30% vs. 26% in favor of everolimus) [Gonzalez-Angulo et al, 2011]. Despite triple negative BC is HER2-, everolimus has been examined in a regimen with anti-HER2 agents since EGFR is high-amplified in $50% of triple negative BC tumors [Reis-Filho and Tutt, 2008;Simon et al, 2016], providing a robust rationale for exploration the association between an anti-EGFR and a mTOR inhibitor to determine overlap in the tumors that were refractory to anti-EGFR drugs [Gogineni and DeMichele, 2012;Passiglia et al, 2015]. Though the mTOR inhibitors paradoxically stimulate the AKT pathway [Sun et al, 2005], this activation could probably serve as a mechanism for resistance to mTOR inhibitors [Hahn et al, 2009;Jerusalem et al, 2014].…”
Section: Mtor Inhibitors In Bcmentioning
confidence: 99%
“…Breast cancer is a heterogeneous complex of diseases [ 3 ] and can be classified into different subtypes based on biological characteristics (traditional classification systems), or gene expression patterns (molecular classification) [ 4 ]. Triple-negative breast cancer (TNBC) has a distinct aggressive molecular subtype, characterized by lack of progesterone receptor (PR), estrogen receptor (ER), and human epidermal growth factor receptor-2 (HER-2) expression [ 5 ] resulting in poorer outcomes than other subtypes [ 6 ]. Moreover, TNBC can be classified in different subtyping based on gene expression profiling into basal like1, basal-like 2, an immunomodulatory subtype, mesenchymal, mesenchymal stem cell-like and luminal androgen receptor subtype [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding triple-negative breast cancer, EGFR amplification has been reported to occur in approximately 60% of cases when analyzed by silver in situ hybridization, validating this receptor as a target in this malignancy [ 6 ]. The scFv of 806 was fused with PE38 to produce the 806-PE38 immunotoxin [ 33 ]. In vitro analysis indicated that it killed triple-negative breast carcinoma cell lines with EGFR overexpression but not lines that only expressed wildtype EGFR at normal levels [ 33 ].…”
Section: Egfrviii and “Cancer-expressed” Egfrmentioning
confidence: 99%